The data diagnostic method of in the system of residue classes - Krasnobayev, Victor; Koshman, Sergey; Kovalchuk, Dmytro (Національний технічний університет "Харківський політехнічний інститут", 2021)
The subject of the article is the development of a method for diagnosing data that are presented in the system of residual classes (SRC). The purpose of the article is to develop a method for fast diagnostics of data in the SRC when entering the minimum information redundancy. Tasks: to analyze and identify possible shortcomings of existing methods for diagnosing data in the SRC, to explore possible ways to eliminate the identified shortcomings, to develop a method for prompt diagnosis of data in SRC. Research methods: methods of analysis and synthesis of computer systems, number theory, coding theory in SRC. The following results were obtained. It is shown that the main disadvantage of the existing methods is the significant time of data diagnostics when it is necessary to introduce significant information redundancy into the non-positional code structure (NCS). The method considered in the article makes it possible to increase the efficiency of the diagnostic procedure when introducing minimal information redundancy into the NCS. The data diagnostics time, in comparison with the known methods, is reduced primarily due to the elimination of the procedure for converting numbers from the NCS to the positional code, as well as the elimination of the positional operation of comparing numbers. Secondly, the data diagnostics time is reduced by reducing the number of SRC bases in which errors can occur. Third, the data diagnostics time is reduced due to the presentation of the set of values of the alternative set of numbers in a tabular form and the possibility of sampling them in one machine cycle. The amount of additionally introduced information redundancy is reduced due to the effective use of the internal information redundancy tha texists in the SRC. An example of using the proposed method for diagnosing data in SRC is given. Conclusions. Thus, the proposed method makes it possible to reduce the time for diagnosing data errors that are presented in the SRC, which increases the efficiency of diagnostics with the introduction of minimal information redundancy.

Предметом статті є розробка методу діагностики даних, які представлені в системі залишкових класів (СЗК). Метою статті є розробка методу швидкої діагностики даних у СЗК при введенні мінімальної інформаційної надмірності. Задачі: провести аналіз і виявити можливі недоліки існуючих методів діагностики даних у СЗК, дослідити можливі шляхи усунення виявлених недоліків, розробити метод оперативної діагностики даних у СЗК. Методи дослідження: методи аналізу і синтезу комп'ютерних систем, теорія чисел, теорія кодування у СЗК. Отримані наступні результати. Показано, що основним недоліком існуючих методів є значний час діагностики даних при необхідності введення значної інформаційної надмірності у непозиційну кодову структуру (НКС). Розглянутий у статті метод дозволяє підвищити оперативність процедури діагностики при введенні у НКС мінімальної інформаційної надмірності. Час діагностики даних, в порівнянні з відомими методами, скорочується в першу чергу за рахунок усунення процедури перетворення чисел з НКС у позиційний код, а також усунення позиційної операції порівняння чисел. По-друге, час діагностики даних скорочується за рахунок зменшення кількості базисів СЗК, в яких можуть виникнути помилки. По-третє, час діагностики даних скорочується за рахунок представлення набору значень альтернативної сукупності (АС) чисел у табличному вигляді та можливості вибірки їх за один машинний такт. Кількість інформаційної надмірності, що додатково вводиться, зменшується за рахунок ефективного використання внутрішньої інформаційної надмірності, яка існує у СЗК. Наведено приклад використання запропонованого методу діагностики даних у СЗК. Висновки. Таким чином, запропонований метод дозволяє скоротити час діагностики помилок даних, що представлені у СЗК, та підвищує оперативність діагностики при введенні мінімальної інформаційної надмірності.
Метод діагностики даних у системі залишкових класів
Keywords: number system; non-positional code structure; computer system; система числення; непозиційна кодова структура; комп'ютерна система